The influence of the physical environment of Class III inpatient rooms on patient satisfaction at Tgk Abdullah Syafi'i Beureunuen Hospital - Devi Hismayani; Yohanna Agatha Sianipar (International Journal on ObGyn and Health Sciences, 2024)
Omega-3 fatty acids have garnered attention for their potential benefits in cardiovascular health and reproductive wellness. This study aimed to investigate the effects of omega-3 supplementation on blood cholesterol levels and ovulation events in trained individuals. A randomized controlled trial was conducted, involving physically active individuals aged 18-45 years engaged in regular exercise training. Participants were randomly assigned to receive either omega-3 supplementation or placebo for a specified duration. Blood lipid profiles, including total cholesterol, LDL-C, HDL-C, and triglyceride levels, were assessed using standardized laboratory assays. Ovulation events and menstrual cycle characteristics were monitored through hormonal assays, ultrasonographic imaging, and menstrual cycle tracking. Analysis of the findings revealed significant reductions in triglyceride levels following omega-3 supplementation, accompanied by trends towards improved LDL-C/HDL-C ratio. Moreover, enhancements in ovulatory function and menstrual cycle regularity were observed in physically active women receiving omega-3 supplementation. These findings underscore the potential benefits of omega-3 supplementation for optimizing cardiovascular and reproductive health outcomes in trained individuals. Future research endeavors should focus on elucidating the underlying mechanisms and conducting longitudinal studies to assess the sustained impact of omega-3 supplementation on health and performance in physically active populations.